Analisis Penerapan Aplikasi Sistem Keuangan Desa (SISKEUDES) Dalam Peningkatan Kualitas Akuntabilitas Keuangan Desa Di Desa Karangrejo Kecamatan Selomerto - Oktavianindita Putri Utami; Erni Agustin; Nuwun Priyono (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the implementation of SISKEUDES in improving the quality of village financial accountability in Karangrejo Village, Selomerto District. This research uses descriptive method with qualitative analysis using the implementation model. Data collection was carried out by library research, observation, and in-depth interviews. The research location is in Karangrejo Village, Selomerto District, Wonosobo Regency. Data analysis uses data reduction, data presentation, and data verification or conclusions. The results showed that the management of the SISKEUDES application in Karangrejo Village, Selomerto District, Wonosobo Regency had been carried out in an accountable manner. performance indicators. With the SISKEUDES application, the village government is greatly assisted in managing village finances and budgets and also provides accuracy in reports that have been made and upholds reporting transparency and accountability.